Modification and Performance Analysis of Small Agricultural Engines Fueled with Producer Gas - Nigran Homdoung (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research was carried out to modify of small diesel engines into spark ignited engines with producer gas as fuel. The objectives were to study effect of combustion chamber type, compression ratio, engine speed and load on engine performance, exhaust emission, fuel cost and to apply mathematical model to predict performance of SI producer gas engine. The original engines before modification were small agricultural diesel engines; having four strokes and 598 CC. Modification was performed for combustion chamber, CR, ignition system and air gas mixer. Producer gas was derived from longan charcoal with mean calorific value of 4.64 MJ/Nm3. The experiments were carried out for bath tub and cavity combustion chambers with varied CR of 9.7:1, 14:1 and 17:1. The engine speed was 1100, 1300, 1500, 1700 and 1900 rpm and load was 20 %, 40 %, 60 %, 80 % and 100 %. The performance of engine was evaluated for torque, brake power, BTE, BSFC, BSEC, and exhaust emission, and compared with diesel engine on similar experiment condition. It was found that the modified engine was able to operate with producer gas successfully. Smooth, operation stability and continuous running were obtained. The COV of engine was between 1.75 to 3.0 %. Maximum performance of engine in bath tub combustion chamber occurred at 14:1 of CR, 1700 rpm, 40 BTDC on full load with torque, brake power, BTE, and BSFC of 18.61 Nm, 3.31 kW, 18.77 % and 0.94 kg/kWh, respectively. For the cavity combustion chamber, the maximum performance of engine occurred at similar conditions to bath tub combustion chamber, except, the ignition timing was at 45 BTDC. The torque, brake power, BTE, and BSFC of 18.05 Nm, 3.21 kW, 23.90 % and 0.74 kg/kWh, respectively, were obtained, while for diesel engine, the torque, brake power and BTE were 26.49 Nm, 4.71 kW and 26.95 %, respectively, compared with producer gas engine at similar test condition. The fuel cost of producer gas engine was lower than diesel engine, while, exhaust emissions were similar. The mathematical model gave good agreement with experimental results and can predict the performance of the gas engine well. The differences were within 6.5 %.